Genetic variability and performance of Asian swamp eel Monopterus albus (Zuiew, 1793) from West Java cultured in saline water medium - Dinar Tri Soelistyowati; Ahmad Fahrul Syarif; Ridwan Affandi; Dendi Hidayatullah (Jurnal Akuakultur Indonesia)
ABSTRACT